Diversity of Essential Oil‐Secretory Cells and Oil Composition in Flowers and Buds of Magnolia sirindhorniae and Its Biological Activities. Issue 1 (17th December 2020) - Ghosh, Dipayan; Chaudhary, Neha; Uma Kumari, K.; Singh, Jyoti; Tripathi, Prakhar; Meena, Abha; Luqman, Suaib; Yadav, Anju; Chanotiya, Chandan Singh; Pandey, Gyanesh; Kumar, Narendra
Abstract: Magnolia sirindhorniae Noot. & Chalermglin produces fragrant flowers. The volatile oil secretary cells, quantity and quality as well as antioxidant and antimicrobial activities of the oils extracted from buds and flowers, have been investigated. The distribution of essential oil secretory cell in bud and flower revealed that the density and size of the oil cells were significantly higher in flowers compared to buds. In different floral parts, carpel has a higher oil cell density followed by gynophore and tepal. The histochemical analysis revealed the essential oil is synthesized in oil secretory cells. The volatile oil yield was 0.25 % in the buds and 0.50 % in flowers. GC/FID and GC/MS analysis identified 33 compounds contributing 83.2–83.5 % of the total essential oil composition. Linalool is the main constituent contributing 58.9 % and 51.0 % in the buds and flowers oils, respectively. The essential oil extracted from the flowers showed higher antimicrobial efficacy against Klebsiella pneumoniae and Staphylococcus aureus . Similarly, the essential oil isolated from the flowers depicts higher free radical scavenging, and antioxidant activity compared to buds' oil. Abstract :